Development of Virtual Resistance Meters using LabVIEW - Suman Lata; H. K. Verma; Puja Kumari (Institute of Advanced Engineering and Science, 2018)
This paper presents the development of three virtual resistance meters using LabVIEW. The unknown resistance is measured in terms of a known resistance of high accuracy by employing (a) a real dc voltage source, (b) a real dc current source, and (c) a virtual dc voltage source. In each case, ratio of two voltage signals is acquired by a single-ADC based multichannel data acquisition card. Therefore error of the ADC gets cancelled, when ratio of two voltages is used in the final calculation of the value of unknown resistance. The first two VRMs use a real excitation source and are thus semi-virtual instruments, whereas the third one is fully-virtual as the excitation source is also implemented in the LabVIEW software along with DAC section of the data acquisition card. The three virtual resistance meters have been successfully implemented. The principle of ratio-metric measurement used makes the accuracy (uncertainty) of final measurement free from the uncertainties of the ADC, the DAC and the excitation source. Standard deviations of the readings taken with the three VRMs have been evaluated and compared. It is concluded that the fully-virtual instrument has the lowest and excellent value of standard deviation.